Schistura obliquofascia, a new loach from Uttarakhand, India (Cypriniformes: Nemacheilidae) - Lokeshwor, Y.; Barat, A.; Sati, J.; Darshan, A.; Vishwanath, W.; Mahanta, P. C. (Zootaxa, 2012)
A new nemacheilid loach, Schistura obliquofascia, is described from Kalsa, a stream near Chanfi, tributary of Gola River,Ganga basin in Uttarakhand, India. The new species is readily distinguished from congeners by the following combinationof characters: 12–14 oblique olivaceous dark bars on the body and three rows of black spots on the dorsal fin; lateral linecomplete with 104–112 pores, dorsal fin with 3–4 simple and 8½ branched rays; 8+8 branched rays in caudal fin; dorsaladipose crest prominent; males lacking suborbital flap; and 10–11 pores in preoperculo-mandibular canal. The sequence of the cytochrome b gene of length 307 base pairs was used for molecular characterization of the species.